Paclobutrazol And Cytokinin Regulation On Culm Growht Of Black Rice (Oryza sativa L. “Cempo Ireng”) - Darussalam Darussalam; Kumala Dewi (Bioeksperimen: Jurnal Penelitian Biologi, 2022)
Rice is a staple food for the majority of Asians; nevertheless, black rice has not been commonly consumed among them. The components of the yield will be determined by the allocation of photosynthate on rice and the tall phenotype of black rice, which is a significant contributing factor to lodging. The growth inhibitor paclobutrazol prevents the manufacture of gibberellin, which results in the tall phenotype of black rice. The endogenous cytokinin content is high at the beginning of the grain filling and then rapidly decreases after that. The purpose of the study was to compare the effects of paclobutrazol and cytokinin on culm height, internode length, culm diameter, lodging resistance, culm parenchyma cell arrangement, and flag leaf structure. Throughout the inquiry, Cempo Ireng black rice cultivar seeds were employed. The seeds were planted in plastic containers that held 10 kg of soil for growth medium and organic fertilizer, and a random block pattern was used for the experiment's design. At 10 weeks following sowing, paclobutrazol was sprayed as a foliar application at concentrations of 0, 50, and 100 ppm. By injecting the kinetin diluted in 0.8 percent agar gel at a rate of 10-5 M in the flag leaf internode lacuna twice, separated by two days, two weeks after anthesis. Eight replications and six combinations were made. DMRT and the significant different were used in the statistical analysis of the mean comparisons (P=0.05). Plant height and internode length were decreased by paclobutrazol (100 ppm), although internode diameter was raised and lodging resistance was induced. The organization of the parenchyma cells in the culm (100 ppm packlobutrazol) changed, and the cells were small and lacked intercellular gaps.